2013
DOI: 10.1016/j.rmed.2012.09.023
|View full text |Cite
|
Sign up to set email alerts
|

The complex link between severity of asthma and rhinitis in mite allergic patients

Abstract: A link between respective severities of rhinitis and asthma was found in only half of mite allergic patients with rhinitis and asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 28 publications
0
10
0
1
Order By: Relevance
“…In the persistent-asthma group, the nasal symptom scores were significantly higher than in the nonpersistent-asthma group. In some studies asthma severity has been associated with rhinitis severity [7,42] , whereas in others the link between asthma and rhinitis severity has been less clear [9] . In our study, the number of blood eosinophils was increased in asthmatics despite concurrent AR, this being more prominent in the persistent-asthma group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the persistent-asthma group, the nasal symptom scores were significantly higher than in the nonpersistent-asthma group. In some studies asthma severity has been associated with rhinitis severity [7,42] , whereas in others the link between asthma and rhinitis severity has been less clear [9] . In our study, the number of blood eosinophils was increased in asthmatics despite concurrent AR, this being more prominent in the persistent-asthma group.…”
Section: Discussionmentioning
confidence: 99%
“…The existence and severity of AR have been linked to the severity of the coexisting asthma [6,7] , although some studies have not confirmed this association [8,9] . The inflammatory process in the airways displays several common characteristics in asthma and AR, e.g.…”
mentioning
confidence: 99%
“…Indeed, the severity of asthmatic rhinosinusitis was positively related to the number of eosinophils in induced sputum as well as in the peripheral blood [5]. Interestingly, asthma was more severe when chronic rhinosinusitis was also present [13]. Moreover, our present study shows that the occurrence of EOM in asthma patients with chronic rhinosinusitis was dependent on the severity of asthma.…”
Section: Discussionmentioning
confidence: 54%
“…Our total patients showed a relatively high rate (34%) of EOM involvement. This might be explained by the severity of asthma in the patients with chronic rhinosinusitis enrolled in this study having been higher than that in the general asthma patient population, because asthma is more severe when chronic rhinosinusitis is also present [13]. …”
Section: Discussionmentioning
confidence: 99%
“…The overlap between allergic and non-allergic upper airways diseases has been discussed in clinical studies, but its epidemiological results remain controversial and poorly defined [13,14,15]. This study aimed to evaluate the prevalence of AR, AR with sinusitis without NP (AR + SsNP) and AR with sinusitis with NP (AR + SwNP), and investigate whether the interaction between AR and bronchial asthma is affected by concomitant upper airway diseases.…”
Section: Introductionmentioning
confidence: 99%